Character Education in a Simple School (Situs Study at SDIT AlMadinah Kartasura) - Suripno , Suripno (2012)
Based on the fact that there are still many school that haven't succesfully educate the learner yet, more over the school with a simple condition is "SDIT Al Madinah Kartasura". A simple school which managed well, with a good characteristic of teacher and staff, that inspired the learners and finally it can influence the behaviour of the learners. The learners who have accustom to obey the rule, discipline, and have a good character at school will automatically have a good way of communicate behaviour in their familiy and society. This research is done for 3 purposes: (1) describing the characters values that is taught in SDIT Al Madinah Kartasura, (2) describing the planning of the educational characters in SDIT Al Madinah Kartasura, (3) describing the helding of educational characters in SDIT Al Madinah Kartasura. The type of the research is analitative research. The research that is lead by the facts, that is found in the formal institution. The analysis of the data is inductively, then constructed to be the hypothesis and theory. The desain that is used is etnography method. The etnography use the step of education final research. The research is done in SDIT Al Madinah Kartasura. The researcher as the instrument. The data is in the vocabulary, action, and document (written data research). The technique to collect the data is using observation, interview, and documents. The data analysis done when we are in the process of teaching or outside the class. The validity of the data is real, valid, and objective. The research results consist of 3 things, (1) the characters value that is taught is formal values and the school custom values, (2) the planning of the helding educational characters that is planned implisitely in the school activity or program and school's rules, (3) the holding of the characters educational that is planned based on the activity program and the good character. The implementation of the holding of educational standard process is better if we completed with the content standard of education. To make the success of the student character building, it is needed to increase the school setting, class setting or the educational standard implementation.